Civil Society: The Worthy Soul of Democracy - Dahal, Dev Raj (Journal of Political Science, 2022)
This is a public lecture delivered in a symposium jointly organized by Surya Ratna Shakya Foundation, Pokhara and Department of Political Science, Prithvi Narayan Campus, Pokhara on December 12, 2021.